ANALISIS DAMPAK ELECTRONIC DATA PROCESSING DALAM PROSES AUDIT INTERNAL BAGI AUDITOR INTERNAL PT BANK SULUTGO - Mandagi, Reynaldi R.; Pangemanan, Sifrid S.; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2018)
Electronic Data Processing (EDP) is the use of automated methods for commercial data processing. As part of information technology, EDP performs repeated data processing of similar data with relatively simple forms of processing. Standar Profesional Akuntan Publik (SPAP) also emphasizes the need for auditor's understanding in examining a computer-based accounting system. This technique in Indonesian is known as Teknik Audit Berbantuan Komputer (TABK) or Computer Assisted Audit Techniques (CAATs) set forth in PSA No. 59 on Computer Assisted Auditing Techniques (SA Section 327). The method used in this study is a qualitative descriptive method by collecting and analyzing data and then drawing conclusions. The results obtained show that young auditors are more adaptable to the development of information technology, especially in conducting computerized internal audit and control. Impacts given in the audit process include increasing independence for internal auditors, providing accuracy and speed in managing data, and producing output from more accurate audit data processing. Impact on internal controls is to make the auditor perform internal control procedures after applying the EDP in the audit process to minimize the possibility of process errors, secure the program and data, and control the audit process to ensure that the audit has been properly implemented. The audit process using EDP is faced with several risks such as errors in data processing caused by human error, data loss caused by computer problems, and the computer used is exposed to the virus.Keywords : Analysis, Electronic Data Processing, Internal Audit